Childbirth Education and Support During Labour: Association with Birth Satisfaction - A.D. Suarez; L.A. Shraibman; V.A. Yakupova (Moscow State University of Psychology and Education, 2023)
The purpose of this study was to compare the effectiveness of antenatal education and individual labour support in the context of the actual experience of childbirth and its psychological perception. Types of antenatal education and individual labour support were analysed in relation to the childbirth experience (mode of delivery, number of medical interventions, obstetric violence, satisfaction with childbirth, physical well-being of women after childbirth). In February-March 2021, we conducted an online survey of 1645 mothers of infants aged 0-13 months. As a result, it was found that preparation for childbirth has no direct relationship with the mode of delivery, the woman's well-being after childbirth and the birth satisfaction. However, preparation for childbirth is associated with fewer medical interventions. Women who gave birth without individual support were less satisfied with their births, more likely to experience obstetric violence, more likely to give birth via caesarean section, with more medical interventions. Thus, support during labour is a safe way to improve the experience of childbirth and the quality of life for mothers in general.